Roland Barthes' Semiotic Analysis of Visual Symbols on the website haveaniesday.com: Myth and Ideology Digital Design - Muhammad Tegar Saputra; Muhammad Fauzi; Mutiara Ramadhani (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
The objective of this research is to deconstruct the mechanisms by which the website's visual design constructs and conveys meaning, utilizing the semiotic framework developed by Roland Barthes. This inquiry specifically investigates how visual symbols operate beyond their overt messages to reproduce and reinforce values that are widely accepted as given. Adopting a qualitative interpretative method, the study applies Barthes' critical semiotic analysis across three levels of meaning: denotation, connotation, and myth. Results show that the figure of a bespectacled owl functions as a signifier for the intelligent